IMPLEMENTASI METODE PERMAINAN BISIK BERANTAI UNTUK MENINGKATKAN ISTIMA’ DI KELAS VIII MTS ASSUNNIYYAH KENCONG JEMBER - Zainuri; Siti Nur Jannah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Abstract In learning Arabic, teachers generally only convey the lecture method or only use one method and students tend to get bored. the teacher also only conveys the main things that are considered important only in language without any practice of what is learned, therefore the media is present as one of the components supporting the success of the teaching and learning process. the researcher chose one of the media, namely chain whisper media because it was considered effective and helpful for students of class 8 MTS in improving students' listening and speaking skills. With the aim to find out how student activities, students' istima development and to find out how the results of the implementation of Whispers in Chains on class VIII students of mts assunniyyah Using descriptive qualitative methods, types of field research, technical data analysis using data reduction, and data validity, namely triangulation of the application of the whisper method chain, makes students more active and not bored, in training language skills makes it easier for students to receive material and information, especially in maharah istimak, and creates a sense of cooperation between students so that the atmosphere of learning activities is not burdensome. The influence of significant student learning outcomes in learning makes this method acceptable. Keywords: method, chain whisper game, istima’.